Detection of Mycoplasma hyopneumoniae by polymerase chain reaction in swine presenting respiratory problems - Yamaguti, M. (Sociedade Brasileira de Microbiologia, 2008)
Since Mycoplasma hyopneumoniae isolation in appropriate media is a difficult task and impractical for daily routine diagnostics, Nested-PCR (N-PCR) techniques are currently used to improve the direct diagnostic sensitivity of Swine Enzootic Pneumonia. In a first experiment, this paper describes a N-PCR technique optimization based on three variables: different sampling sites, sample transport media, and DNA extraction methods, using eight pigs. Based on the optimization results, a second experiment was conducted for testing validity using 40 animals. In conclusion, the obtained results of the N-PCR optimization and validation allow us to recommend this test as a routine monitoring diagnostic method for Mycoplasma hyopneumoniae infection in swine herds.